Patient-Centred Coordinated Care in Times of Emerging Diseases and Epidemics - Borycki, E.; Cummings, E.; Dexheimer, J. W.; Gong, Y.; Kennebeck, S.; Kushniruk, A.; Kuziemsky, C.; Saranto, K.; Weber, J.; Takeda, H. (Yearbook of Medical Informatics, 2015)
Objectives: In this paper the researchers describe how existing health information technologies (HIT) can be repurposed and new technologies can be innovated to provide patient-centered care to individuals affected by new and emerging diseases.Methods: The researchers conducted a focused review of the published literature describing how HIT can be used to support safe, patient-centred, coordinated care to patients who are affected by Ebola (an emerging disease).Results: New and emerging diseases present opportunities for repurposing existing technologies and for stimulating the development of new HIT innovation. Innovative technologies may be developed such as new software used for tracking patients during new or emerging disease outbreaks or by repurposing and extending existing technologies so they can be used to support patients, families and health professionals who may have been exposed to a disease. The paper describes the development of new technologies and the repurposing and extension of existing ones (such as electronic health records) using the most recent outbreak of Ebola as an example.
Keywords: Patient safety; health information technology; Ebola virus; electronic health records; technological innovations